Analisis Kepraktisan E-module Kalor dan Perpindahannya Berbasis Problem Based Learning (PBL) - Euis Puspitasari; Baskoro Adi Prayitno; Lina Mahardiani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The purpose of this study is to analyze the practicality of a Problem-Based Learning (PBL)-based e-module on the topic of Heat and Its Transfer. This research employed the Research and Development (R&D) method using the 4D development model, which was limited to the development (Develop) stage. The participants of the study consisted of 3 science teachers and 32 Grade VII students from SMP Negeri 2 Tambakrejo, selected through a random sampling technique. Data were collected using questionnaire instruments distributed to both the science teachers and the students. The data were analyzed using a descriptive qualitative approach by calculating the average scores of the quantitative results. The findings revealed that the practicality test conducted by science teachers produced an average percentage of 94.74%, while the students’ responses reached 96.37%, both of which fall under the "very practical" category. These results indicate that the PBL based e-module on Heat and Its Transfer is highly practical and appropriate for use in the teaching and learning process.